Selected Essays in Stock Market Liquidity. Innovative XLM Measure at the Frankfurt Stock Exchange: Cloudy Skies, Time of the Day and the Role of Designated Sponsors for Stock Market Liquidity. - Tatjana Verrier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2010)
This dissertation is built around three separate papers that research several aspects of stock market liquidity. All three papers use the innovative XLM (Exchange Liquidity Measure) data to measure the liquidity. The first paper entitled Does Screen Trading Weather the Weather? A Note on Cloudy Skies, Liquidity and Computerized Stock Markets tests for the presence of a weather effect on liquidity in a screen-based electronic stock market. The empirical evidence suggests that cloudy skies correspond with high natural liquidity levels and low liquidity injected by market makers. This result is consistent with findings for floor-based stock trading and with the hypothesis that market makers add less value in markets with high natural liquidity. The second paper entitled Designated Sponsors on Xetra – Is One Designated Sponsor Enough? tests for the impact of Designated Sponsors on liquidity in the electronic trading system Xetra at the Frankfurt stock exchange. The empirical results suggest that Designated Sponsors improve liquidity and that the increase in a number of Designated Sponsors improves liquidity further. The third paper entitled How Do Trading Costs Vary Across the Day? A note on the innovative XLM measure for Small Caps at the Frankfurt Stock Exchange provides empirical evidence on the intraday pattern of trading costs for German small cap stocks in the electronic trading system Xetra. The empirical evidence for the TecDAX stocks under investigation suggests a reverse-J shaped intraday profile for execution costs. Thus, trading is most expensive in the first 30 minutes after Xetra opens, and it is cheapest at the time when the NYSE starts trading. We conclude that cross-border integration of stock exchanges fosters market quality.
urn:nbn:de:101:1-201011262903; Additional information: zugl. Dissertation, European Business School, 2010
Keywords: G10; G12; G14; 330; Liquidity; stock market; XLM; Xetra; weather; Designated sponsors; intraday; market makers